Atlas of pediatric oral and dental developmental anomalies - Ansari, Ghassem; Golpayegani, Mojtaba Vahid; Welbury, Richard (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
A quick reference diagnostic guide for students and clinicians, covering a wide range of oral and dental developmental anomalies in children and adolescents Written by world-renowned pediatric dentists, this easily accessible, well-illustrated reference covers a wide range of oral and dental developmental anomalies in children and adolescents, and includes rare as well as more common conditions. Divided into two parts, the first part is dedicated to normal tissue initiation, formation, and development in the orodental region. The second part offers comprehensive pictorial descriptions of each condition and discussions of the treatment options available.-A useful, quick reference atlas helping students and clinicians diagnose a wide range of oral and dental developmental anomalies in children and adolescents -Highly illustrated with clinical photographs -Describes both common and rare conditions, and explores treatment options Atlas of Pediatric Oral and Dental Developmental Anomalies is an excellent resource for undergraduate dentistry students, postgraduate pediatric dentistry students, and pediatric dental practitioners.
Oral and dental anatomy -- Histology and embryology of the tooth and periodontium -- Epidemiology and diagnosis of teeth development disturbances -- Etiology and pathology of teeth disturbances -- Eruption disturbances of teeth : etiology and diagnosis -- Self evaluation cases.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 06, 2019).
Keywords: Mouth -- Abnormalities -- Atlases; Teeth -- Abnormalities -- Atlases; Pedodontics -- Atlases; Mouth Abnormalities -- diagnosis; Mouth Abnormalities -- etiology; Tooth Abnormalities -- diagnosis; Tooth Abnormalities -- etiology; Child; Adolescent; Atlas; Electronic books